Pelatihan Strategi Pemasaran Untuk Produk Rupa Olahan Serbuk Kayu Bagi Terdampak Pandemik di Yayasan Rumah Sinergi Indonesia - Iyus Wiadi; Ayoeningsih Dyah Woelandhary; Gilang Cempaka; Ira Samri (Jurnal Pengabdian Pada Masyarakat, 2022)
MARKETING STRATEGY TRAINING FOR WOOD POWDER PROCESSED FINE PRODUCTS FOR THE IMPACTED OF THE PANDEMIC AT THE RUMAH SINERGI INDONESIA FOUNDATION. This community service program aims to provide education, knowledge of marketing strategies and assistance in the manufacture of decorative products from sawdust waste. The participants of this training program are 11th grade students and employees of the Rumah Sinergi Indonesia Foundation. This training provides an increase in the ability of participants to be able to sell products according to market segmentation. This program is a form of scientific development from aspects of management and product design needed by the community. The results of this PKM program show the motivation and enthusiasm of the participants as well as a higher sense of learning from the participants. This is shown from the results of the survey on the benefits of insight after receiving training. The results of this training are very useful for participants in mapping out marketing strategies. This program is expected to be continued with various business needs in product quality and marketing effectiveness.